2004
DOI: 10.1158/1078-0432.ccr-04-0941
|View full text |Cite
|
Sign up to set email alerts
|

mTOR and P70 S6 Kinase Expression in Primary Liver Neoplasms

Abstract: Purpose: mTOR and P70 S6 kinase (S6K) play a key role in regulating protein translation. The role of mTOR and S6K in hepatocellular carcinoma has not been investigated, but this pathway is of particular interest because an effective inhibitor, rapamycin, is available. This study was undertaken to determine the prevalence and clinicopathological correlates of mTOR pathway activation in hepatocellular carcinoma and to determine whether rapamycin inhibits the pathway in cell culture.Experimental Design: Total and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
234
1
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(253 citation statements)
references
References 16 publications
13
234
1
5
Order By: Relevance
“…High tumor proliferation induced by ERK activation is closely linked to chemotherapy resistance (28). Because the blockage of a MEK/ERK pathway can be overcome by other molecular abnormalities, including Janus-activated kinase/signal transducers and activators of transcription (22), focal adhesion kinase (41), and the mammalian target of rapamycin (42), it is likely that HCC could develop resistance to MEK inhibitors. The clinical effectiveness of inhibitors of the MEK/ERK pathway may be limited when administered alone, as HCC tumors possess more than one genetic defect (43).…”
Section: Discussionmentioning
confidence: 99%
“…High tumor proliferation induced by ERK activation is closely linked to chemotherapy resistance (28). Because the blockage of a MEK/ERK pathway can be overcome by other molecular abnormalities, including Janus-activated kinase/signal transducers and activators of transcription (22), focal adhesion kinase (41), and the mammalian target of rapamycin (42), it is likely that HCC could develop resistance to MEK inhibitors. The clinical effectiveness of inhibitors of the MEK/ERK pathway may be limited when administered alone, as HCC tumors possess more than one genetic defect (43).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of p70S6K and dysregulation of eIF4E have been observed in many tumors and cancer cells, [29][30][31] and overexpression of both eIF4E and 4EBP1 in gastrointestinal carcinomas has been reported. 32 However, we found that AFPGC cells were different from CGC cells in that cisplatin minimally affected the phosphorylation of p70S6K and 4EBP1.…”
Section: Discussionmentioning
confidence: 99%
“…S3 A-D). Increased expression of mTOR protein has been reported for several types of human tumors, including colon cancer (22,23), and reduced expression of mTOR protein impairs the mTORC1 signaling (2).…”
Section: Inhibitory Effect Of Rad001 On Polyp Formation Is Attributabmentioning
confidence: 99%